IS SLOW ECONOMIC GROWTH ORIGINATING FROM THE TOTAL EXTERNAL DEBT STOCK IN DEMOCRATIC REPUBLIC OF CONGO? - MUPENDA, Olivier Munene (Theoretical and Practical Research in Economic Fields; Vol 12 No 1 (2021): TPREF, Volume XII, Issue 1(23), Summer 2021, 2021)
Unsustainable debt reduces the productivity of a country. Ten years following its “1960 independence”, the Democratic Republic of Congo adopted policies that resorted to external finances while the world was at the peak of the 1970 Petro-dollar crisis. The following decade, in the 1980’s, with the fall in price of raw materials, the Democratic Republic of Congo was trapped in an unsustainable debt burden cycle that stagnated its economy and according to the World Bank data, reduced its GDP per Capita. The rise of active armed conflicts in the 1990’s and political unrest during the 2000's added pressures to resort to further financial support from external creditors, facilitating corruption and poverty in the process. The inability to service debts leads to economic consequences. One of these consequences is reduction in productivity. With empirical evidence, our analysis will be looking at the Congolese productivity from independence in 1960 to the historical democratic transfers of power in late 2018 to understand the effects of external debts in its economic growth.